The RAGE expression in glomerulus and the Malondialdehyde level in the kidney of Diabetes Mellitus rat model after exercise - Anita, Diyah Candra; Sulistyorini, Sri Lestari; Kadarsih, Sri (Bangladesh Journal of Medical Science, 2019)
Background: The main cause of complications in diabetes mellitus is a condition of oxidative stress due to increased reactive oxygen species (ROS). The increase in ROS can be triggered by the increase in advanced glycation end-products (AGE), which binds to its receptor (RAGE). The result of increased ROS will lead to lipid peroxidation in cell membranes and induce particular increase in malondialdehyde (MDA). Objectives: The objective of this study was to evaluate the benefits of physical exercise in preventing complications of the kidneys caused by hyperglycemia. Method: This study was a pure experimental research with post-test only group design. Subjects were 10 male Sprague Dawley rats induced with 35 mg/kgdose of streptozotocin (STZ). The subjects were divided into two groups, i.e. the STZ group and STZ group with physical exercise. Physical exercise was given in 9 weeks using a treadmill, in 5 times/week frequency, moderate intensity, 0 degree of tilt, gradually increased speed and duration. Result: Regular and measurable physical exercise can decrease the blood glucose level(0,048) and reduce the RAGE expression in glomerulus(0,003) but increase MDA level in kidney (0,767). Conclusion: Regular and measurable physical exercise can decrease the blood glucose level and reduce the RAGE expression in glomerulus. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.484-490